Изучение аллергизирующих свойств радиофармпрепарата "Наноколлоид, 99mTc-Al2o3" в эксперименте - Варламова Н. В. Наталья Валерьевна; Стасюк Е. С. Елена Сергеевна; Тицкая А. А. Анна Александровна; Синилкин И. Г. Иван Геннадьевич; Ларионова Л. А. Людмила Александровна; Шерстобоев Е. Ю. Евгений Юрьевич; Трофимова Е. С. Евгения Сергеевна; Лигачева А. А. Анастасия Александровна; Скуридин В. С. Виктор Сергеевич (биомедицинские исследования, 2015)
Заглавие с экрана